Photophysical and Electrochemical Properties and Anticancer Activities of Porphyrin-Cored Fluorenodendrimers Synthesized by Click Chemistry - Anandkumar, Devaraj; Rajakumar, Perumal (Synlett, 2018)
A new class of porphyrin-cored fluorenodendrimers were synthesized by a convergent approach through click chemistry. The zeroth-, first-, and second-generation porphyrin-cored fluorenodendrimers were characterized by means of 1H and 13C NMR spectroscopy, UV-vis spectroscopy, fluorescent spectroscopy, elemental analysis, and MALDI-TOF mass spectrometry. The UV-vis spectrum of the dendrimers showed an increase in the absorption intensity on increasing the dendrimer generation, and a bathochromic shift was observed for higher-generation dendrimers compared with lower-generation dendrimers. The dendrimers showed emission bands at 317, 604–668, and 617–668 nm, the intensity of which increased with increasing dendrimer generation. All the synthesized dendrimers exhibited a reversible oxidation potential in cyclic voltammetry. The therapeutic efficacy of the porphyrin-cored fluorenodendrimers for the inhibition of a growth tumor cell (PA-1) increased with increasing generation number of the dendrimer.
Keywords: dendrimers; fluorenes; click chemistry; porphyrin; anticancer activity